2002
DOI: 10.1080/ejc.7.1.41.52
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric morbidity and socio-demographic factors in rural West Bengal, India

Abstract: The impact of selected socio-demographic factors on reported obstetric morbidity during antepartum and postpartum periods was studied through a cross-sectional retrospective survey carried out in rural areas of three districts of West Bengal, India. During their most recent live births, 56.6% of mothers reported at least one morbid condition. Mothers with higher levels of education reported fewer overall problems. Factors such as age and pregnancy order affect obstetric morbidity differently in different relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
3
7
2
Order By: Relevance
“…In general terms, it may be expected that rural, less educated, lower caste women from households of low economic status experienced more problems during their last pregnancy because of limited access to health care, low knowledge regarding complications and low health status prior to conception. A previous study found similar results in that religion, level of education and economic status were important parameters determining the prevalence of maternal complications in the study population 12 …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In general terms, it may be expected that rural, less educated, lower caste women from households of low economic status experienced more problems during their last pregnancy because of limited access to health care, low knowledge regarding complications and low health status prior to conception. A previous study found similar results in that religion, level of education and economic status were important parameters determining the prevalence of maternal complications in the study population 12 …”
Section: Discussionsupporting
confidence: 79%
“…Maternal mortality has declined during the last decade, and yet the proportion of maternal complications has been increasing 35 . This may be due to various sociodemographic, economic and health system‐related factors affecting these complications directly or indirectly 12,21,22,35,36 . In this study, we explored the exogenous effects of these factors on maternal complications, that is, the latent constructs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kishan and co-workers observed that timely antenatal care was the essential component in the reduction of perinatal loss 16 . Mukhopadhyay and associates observed, in a recent study for West Bengal, that at least one morbid condition was reported by 56.6% of mothers during antepartum and postpartum periods in their most recent live birth 17 . Mothers with higher levels of education reported fewer overall problems.…”
mentioning
confidence: 96%